WebGIS Wisata Pulau Setokok - Dina Fadila Putri; Farouki Dinda Rassarandi (Politeknik Caltex Riau, 2022)
Batam city is the main route for the entry of Indonesian tourism visits. With a record of foreign tourist arrivals, the third largest number behind Bali and then Jakarta. Setokok Island is administratively included in Bulang District, which is located in Batam City, Riau Islands Province. Setokok Island has 24 islands but only 5 are inhabited. Astronomically, Setokok Island is located on the lines 0.92588⁰N and 104.05856⁰E. Most people and tourists do not know about the existence of tourist objects in Setokok Village, because of the lack of spatial information about the location of tourist objects in Setokok Village. A promotional media is needed to provide information and the existence of Setokok Island attractions. The initial step taken by the researcher was collecting data in the form of data information such as tourism potential, addresses, and existing facilities on Setokok Island. Then a location survey was carried out by selecting the coordinates of each Setokok Island tourist attraction, and continued with data processing and usability testing. The results of the Setokok Island tourism WebGIS test using the SUS (System Usability Scale) method are acceptability ranges with a marginal high predicate, which is interpreted in the form of respondents in the view that this WebGIS has been made well. Then the results of the grade scale with the predicate D and the adjective rating with the predicate good, which means that the Setokok Island tourism WebGIS has been well received by the respondents and is suitable for use.